Інженерія вимог та планування розробки продукту : впровадження хмарних технологій в процеси ІТ-інфраструктури організації - Прилепо, В. Г. (ХНУРЕ, 2023)
Requirements engineering and product development planning is a key step in the software development process. This phase defines the functional and nonfunctional requirements for the product and plans the product development based on these requirements. With the use of cloud technologies, requirements engineering, and product development planning can be significantly improved and optimized. Organizations can reduce the cost of purchasing hardware and software by focusing on the use of cloud services. Therefore, the use of cloud technologies in requirements engineering and product development planning is an important aspect in ensuring efficient and rapid product development.